Thư viện số và cán bộ thư viện số - Đỗ, Văn Hùng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presents a review on digital library (concepts, components, role and development history,) and digital librarians (concept, role of librarians in digital environment,); determines identifies basic knowledge and skills necessary for digital librarians and sets forth some orientations for DL development in the coming time.